Trilogi Wacana Citra Anggota Legislatif PKS di Instagram: Analisis Kritis Komunikasi Politik, Dakwah, dan Personal Branding pada Akun Instagram @endah_purwnti: Studi Kasus Kota Bogor - Dwi Muliati; Dewi Anggrayni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to deconstruct the image construction of a Prosperous Justice Party (PKS) legislator in the digital realm, focusing on how narratives of political communication, da'wah missions, and personal branding are interwoven into a unified discourse. Employing a qualitative method with a case study approach reinforced by an in-depth literature review, this research analyzes the content of the Instagram account @endahpurwnti, a member of the Bogor City Council. Data analysis techniques utilize Norman Fairclough's three-dimensional Critical Discourse Analysis (CDA) model to dissect the dimensions of text, discursive practice, and sociocultural practice. The results indicate the existence of a mutually reinforcing